Clove oil-in-water nanoemulsion: Mitigates growth of Fusarium graminearum and trichothecene mycotoxin production during the malting of Fusarium infected barley. (15th May 2020) - Wan, Jing; Jin, Zhao; Zhong, Shaobin; Schwarz, Paul; Chen, Bingcan; Rao, Jiajia
Graphic abstract: Highlights: Physically stable clove oil nanoemulsions were fabricated using microfluidizer. Clove oil nanoemulsions can inhibit Fusarium growth during malting. Malt Deoxynivalenol was decreased after treated with clove oil nanoemulsion. Tween 80-stablized nanoemulsion displayed less flavor impact on final malt. Abstract: Fusarium mycotoxin contamination in malting barley is of great concerns in malting industry. Our recent study found that clove oil nanoemulsions can act as highly efficient antifungal agents in vitro . Therefore, we explored the efficacy of clove oil nanoemulsions on Fusarium growth and mycotoxin during malting process. The impact of emulsifier types (Tween 80, BSA and quillaja saponins) on the formation of clove oil nanoemulsion, the mitigation effects on mycotoxin levels and fungal biomass, and the clove oil flavor residues on malts were measured. We observed that 1.5 mg clove oil/g nanoemulsion showed a negligible influence on germinative energy of barley, while still efficiently eliminated the DON levels and toxicogenic fungal biomass as quantified by Tri5 DNA content. Tween 80-stablized clove oil nanoemulsion displayed higher mycotoxin inhibitory activity and less flavor impact on the final malt. The results indicated the potential application of essential oil nanoemulsion during the malting process.